A flexible high-conductivity negative electrode sheet, a preparation method and application thereof
Patent Information
- Application Number
- CN202611114979.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-13
AI Technical Summary
然而,受限于各组分物化性质的差异及制备工艺的非理想性,碳纳米管难以在微观硅碳体系中实现均匀分散,常以团聚体形式存在,导致有效导电通路受阻;同时,硅源难以精准填充至多孔碳内部,致使孔隙结构的缓冲效能大打折扣
本发明得到的硅碳负极材料,既能提升多孔碳的导电性;又能充当硅基材料的缓冲基质,以适应硅在锂化过程中的体积膨胀和收缩,不仅增强了导电性和结构稳定性,还改善了容量衰减的问题。
Smart Images

Figure CN122907600A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery anode material preparation technology, specifically relating to a flexible, highly conductive anode sheet, its preparation method, and its application. Background Technology
[0002] Lithium-ion batteries are widely used in electric vehicles, large-scale energy storage, and portable electronic devices, and the market is placing higher demands on their energy density, cycle life, and rate performance. Silicon, due to its ultra-high theoretical specific capacity (4200 mAh / g) and low delithiation potential, is considered a highly promising next-generation high-energy-density anode material. However, silicon undergoes significant volume expansion during charging and discharging (volume change rate can exceed 300%). This significant volume effect leads to the pulverization, breakage, and detachment of active particles from the current collector. The newly exposed silicon surface continuously undergoes side reactions with the electrolyte, causing repeated rupture and regeneration of the solid electrolyte interphase (SEI) film. This not only consumes limited lithium sources and electrolyte but also causes a sharp increase in interfacial impedance, ultimately resulting in low initial coulombic efficiency and rapid degradation of cycle performance.
[0003] To address these issues, existing technologies typically employ a silicon-carbon composite strategy, utilizing carbon materials as a buffer matrix. The carbon layer not only buffers the volume expansion of silicon particles and inhibits direct contact between silicon and the electrolyte but also improves the overall conductivity of the material. However, conventional silicon-carbon composites still struggle to completely suppress the volume expansion stress of silicon particles under high specific capacity or high rate conditions. As cycling progresses, the interfacial bonding between the active material and the conductive matrix is disrupted by repeated volume deformation, leading to electrical contact failure of the active particles and consequently increasing the internal contact resistance of the electrode. This disruption of structural integrity directly blocks electron transport channels, severely limiting the rate performance and long-cycle stability of the anode material.
[0004] Existing technologies attempt to address these challenges by introducing porous carbon buffer matrices and carbon nanotube conductive agents. However, due to the differences in the physicochemical properties of the components and the non-ideal nature of the preparation process, carbon nanotubes are difficult to achieve uniform dispersion in microscopic silicon-carbon systems, often existing as aggregates, which obstructs effective conductive pathways. Simultaneously, silicon sources are difficult to precisely fill the porous carbon interior, significantly reducing the buffering efficiency of the pore structure. More critically, the lack of strong chemical bonds and interfacial synergistic design between the components makes them prone to structural collapse and a sharp increase in interfacial impedance due to volume effects during long-term cycling, resulting in irreconcilable contradictions in improving initial efficiency, rate capability, and cycle life.
[0005] In summary, how to develop a technology that can achieve uniform synergy between silicon, porous carbon, and highly conductive networks (such as carbon nanotubes) at the microscale, and maintain structural integrity through strong interfacial interactions, thereby simultaneously improving the cycle life, rate performance, and first-cycle efficiency of the anode material, is a technical problem that urgently needs to be solved in the field of lithium-ion battery anode materials. Summary of the Invention
[0006] The purpose of this invention is to provide a flexible, highly conductive negative electrode sheet, its preparation method, and its application, so as to solve the problems mentioned in the background art.
[0007] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing a flexible, highly conductive negative electrode sheet, comprising the following steps: S1. Place porous carbon materials and metals (metal oxides) / salts inside a plasma ball milling device, and place the material-carrying area of the ball milling device in an external magnetic field device; S2. The porous carbon is ball-milled in the device for a certain time. During the ball milling process, the magnetic field strength is controlled by an external magnetic field device to obtain pretreated porous carbon A. The mass ratio of the pretreated porous carbon A to the porous carbon material is 1:(1.005-1.35). The pretreated porous carbon A is subjected to low-temperature plasma growth of an ultrathin carbon film under inert gas and carbon source gas to obtain pretreated porous carbon B. The thickness of the outer carbon film of the pretreated porous carbon B is 0.2nm~2nm.
[0008] S3. The pretreated porous carbon B is heat-treated under an inert gas and a carbon source gas to obtain modified porous carbon containing metal (metal oxide) and CNTs formed in situ with the metal as active sites. The BET ratio of the modified porous carbon to the pretreated porous carbon B is 1:(1.05~1.35). The heat treatment temperature is 300℃~900℃.
[0009] S4. The modified porous carbon is heat-treated under inert gas and silicon / carbon source gas to obtain pre-modified silicon-carbon anode material. The BET ratio of the modified porous carbon to the pretreated porous carbon B is (0.35~0.65):1. The heat treatment temperature is 300℃~900℃.
[0010] S5. The obtained silicon-carbon anode material is mixed with binder and conductive agent. During the coating process, the magnetic field strength is controlled by an external magnetic field device to obtain a gradient-distributed silicon-carbon anode sheet. The concentration of metal oxide in the electrode sheet decreases from the outside to the current collector direction by 0.001~0.8 mol / μm. The strength of the magnetic field is 0.002~1.5T.
[0011] Further, in step S4, the ID / IG ratio of the Raman spectrum of the silicon-carbon anode material is 0.85~1.52, the area of the silicon peak / D peak is 0.013~0.027, and the ratio of the area of the silicon peak / G peak in the Raman spectrum is 0.015~0.036. Furthermore, in step S5, the Rct ratio of the electrode after the external magnetic field strength is applied to the electrode relative to the value when no magnetic field is applied is 1:1.5~4.5.
[0012] Further, in step S1, the porous carbon material has a BET value of 1000~3300m. 2 / g, pore volume 0.6~2.5cm 3 / g, with an average pore size of 1.5~2.1nm; Further, in step S1, the mass ratio of the porous carbon material to the metal or salt is (80-98.9):(1~10):(1~10), and the molar ratio of the porous carbon material to the metal or salt is (99~99.8):(0.05~0.1):(0.05~0.1). Furthermore, in step S2, the ball milling time is 0.5~5h, the protective gas is N2 or Ar, and the power output of the equipment is 200~600W; the magnetic field strength of the loading area is 0.03~2T, and the magnetic field attenuation mode is not limited.
[0013] Furthermore, in step S2, the BET of the obtained pretreated porous carbon is 0.1~25m. 2 / g, pore volume 0.7~2.3cm 3 / g.
[0014] Furthermore, in step S3, the aspect ratio of the CNTs grown in situ on the metal site is 0.03~240.
[0015] A flexible, highly conductive negative electrode sheet is prepared using a flexible, highly conductive negative electrode sheet and its preparation method.
[0016] Application of a flexible, highly conductive negative electrode sheet in lithium-ion or sodium batteries.
[0017] Compared with the prior art, the beneficial effects of the present invention are: The silicon-carbon anode material obtained by this invention can not only improve the conductivity of porous carbon, but also act as a buffer matrix for silicon-based materials to adapt to the volume expansion and contraction of silicon during the lithiation process. This not only enhances conductivity and structural stability, but also improves the capacity decay problem. Attached Figure Description
[0018] Figure 1 This is a complex impedance plane diagram of the present invention. Detailed Implementation
[0019] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Furthermore, the technical features involved in the various embodiments of this invention described below can be combined with each other as long as they do not conflict with each other.
[0020] For experiments not specifically described in the examples, the procedures or conditions should be followed according to the conventional experimental procedures described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available conventional reagent products.
[0021] Example 1: A flexible, highly conductive negative electrode sheet and its preparation method, comprising the following steps: S1. Place porous carbon materials and metals (metal oxides) / salts inside a plasma ball milling device, and place the material-carrying area of the ball milling device in an external magnetic field device; S2. The porous carbon is ball-milled in the device for 4.5 hours. During the ball milling process, the magnetic field strength is controlled by an external magnetic field device to obtain pretreated porous carbon A. The mass ratio of the pretreated porous carbon A to the porous carbon material is 1:1.22g. The pretreated porous carbon A is subjected to low-temperature plasma growth of an ultrathin carbon film under inert gas and carbon source gas to obtain pretreated porous carbon B. The thickness of the outer carbon film of the pretreated porous carbon B is 1.3nm.
[0022] S3. The pretreated porous carbon B is heat-treated under an inert gas and a carbon source gas to obtain modified porous carbon containing metal (metal oxide) and CNTs formed in situ with metal as active sites. The BET ratio of the modified porous carbon to the pretreated porous carbon B is 1:1.16. The heat treatment temperature is 600℃.
[0023] S4. The modified porous carbon is heat-treated under inert gas and silicon / carbon source gas to obtain pre-modified silicon-carbon anode material. The BET ratio of the modified porous carbon to the pretreated porous carbon B is 0.65:1. The heat treatment temperature is 600℃.
[0024] S5. The obtained silicon-carbon anode material is mixed with an inert gas, a binder, and a conductive agent. During the mixing process, the magnetic field strength is controlled by an external magnetic field device to obtain a gradient-distributed silicon-carbon anode sheet. The concentration of metal oxide in the electrode sheet decreases by 0.025 mol / μm from the outside to the current collector direction. The strength of the magnetic field is 0.12T.
[0025] Example 2: A flexible, highly conductive negative electrode sheet and its preparation method, comprising the following steps: S1. Place porous carbon materials and metals (metal oxides) / salts inside a plasma ball milling device, and place the material-carrying area of the ball milling device in an external magnetic field device; S2. The porous carbon is ball-milled in the device for 4.5 hours. During the ball milling process, the magnetic field strength is controlled by an external magnetic field device to obtain pretreated porous carbon A. The mass ratio of the pretreated porous carbon A to the porous carbon material is 1:1.22g. The pretreated porous carbon A is subjected to low-temperature plasma growth of an ultrathin carbon film under inert gas and carbon source gas to obtain pretreated porous carbon B. The thickness of the outer carbon film of the pretreated porous carbon B is 1.3nm.
[0026] S3. The pretreated porous carbon B is heat-treated under an inert gas and a carbon source gas to obtain modified porous carbon containing metal (metal oxide) and CNTs formed in situ with metal as active sites. The BET ratio of the modified porous carbon to the pretreated porous carbon B is 1:1.16. The heat treatment temperature is 600℃.
[0027] S4. The modified porous carbon is heat-treated under inert gas and silicon / carbon source gas to obtain pre-modified silicon-carbon anode material. The BET ratio of the modified porous carbon to the pretreated porous carbon B is 0.65:1. The heat treatment temperature is 600℃.
[0028] S5. The obtained silicon-carbon anode material is mixed with an inert gas, a binder, and a conductive agent. During the mixing process, the magnetic field strength is controlled by an external magnetic field device to obtain a gradient-distributed silicon-carbon anode sheet. The concentration of metal oxide in the electrode sheet decreases by 0.032 mol / μm from the outside to the current collector direction. The strength of the magnetic field is 0.14T.
[0029] Example 3: A flexible, highly conductive negative electrode material and its preparation method, comprising the following steps: S1. Place porous carbon materials and metals (metal oxides) / salts inside a plasma ball milling device, and place the material-carrying area of the ball milling device in an external magnetic field device; S2. The porous carbon is ball-milled in the device for 4.5 hours. During the ball milling process, the magnetic field strength is controlled by an external magnetic field device to obtain pretreated porous carbon A. The mass ratio of the pretreated porous carbon A to the porous carbon material is 1:1.22g. The pretreated porous carbon A is subjected to low-temperature plasma growth of an ultrathin carbon film under inert gas and carbon source gas to obtain pretreated porous carbon B. The thickness of the outer carbon film of the pretreated porous carbon B is 1.3nm.
[0030] S3. The pretreated porous carbon is heat-treated under an inert gas and a carbon source gas to obtain modified porous carbon containing metal (metal oxide) and CNTs formed in situ with metal as active sites. The BET ratio of the modified porous carbon to the pretreated porous carbon B is 1:1.16. The heat treatment temperature is 600℃.
[0031] S4. The modified porous carbon is heat-treated under inert gas and silicon / carbon source gas to obtain pre-modified silicon-carbon anode material. The BET ratio of the modified porous carbon to the pretreated porous carbon B is 0.65:1. The heat treatment temperature is 600℃.
[0032] S5. The obtained silicon-carbon anode material is mixed with an inert gas, a binder, and a conductive agent. During the mixing process, the magnetic field strength is controlled by an external magnetic field device to obtain a gradient-distributed silicon-carbon anode sheet. The concentration of metal oxide in the electrode sheet decreases by 0.038 mol / μm from the outside to the current collector direction. The strength of the magnetic field is 0.17T.
[0033] Example 4: A flexible, highly conductive negative electrode sheet and its preparation method, comprising the following steps: S1. Place porous carbon materials and metals (metal oxides) / salts inside a plasma ball milling device, and place the material-carrying area of the ball milling device in an external magnetic field device; S2. The porous carbon is ball-milled in the device for 4.5 hours. During the ball milling process, the magnetic field strength is controlled by an external magnetic field device to obtain pretreated porous carbon A. The mass ratio of the pretreated porous carbon A to the porous carbon material is 1:1.22g. The pretreated porous carbon A is subjected to low-temperature plasma growth of an ultrathin carbon film under inert gas and carbon source gas to obtain pretreated porous carbon B. The thickness of the outer carbon film of the pretreated porous carbon B is 1.3nm.
[0034] S3. The pretreated porous carbon B is heat-treated under an inert gas and a carbon source gas to obtain modified porous carbon containing metal (metal oxide) and CNTs formed in situ with metal as active sites. The BET ratio of the modified porous carbon to the pretreated porous carbon B is 1:1.16. The heat treatment temperature is 600℃.
[0035] S4. The modified porous carbon is heat-treated under inert gas and silicon / carbon source gas to obtain pre-modified silicon-carbon anode material. The BET ratio of the modified porous carbon to the pretreated porous carbon B is 0.65:1. The heat treatment temperature is 600℃.
[0036] S5. The obtained silicon-carbon anode material is mixed with an inert gas, a binder, and a conductive agent. During the mixing process, the magnetic field strength is controlled by an external magnetic field device to obtain a gradient-distributed silicon-carbon anode sheet. The concentration of metal oxide in the electrode sheet decreases by 0.030 mol / μm from the outside to the current collector direction. The strength of the magnetic field is 0.22T.
[0037] Example 5: A flexible, highly conductive negative electrode sheet and its preparation method, comprising the following steps: S1. Place porous carbon materials and metals (metal oxides) / salts inside a plasma ball milling device, and place the material-carrying area of the ball milling device in an external magnetic field device; S2. The porous carbon is ball-milled in the device for 4.5 hours. During the ball milling process, the magnetic field strength is controlled by an external magnetic field device to obtain pretreated porous carbon A. The mass ratio of the pretreated porous carbon A to the porous carbon material is 1:1.22g. The pretreated porous carbon A is subjected to low-temperature plasma growth of an ultrathin carbon film under inert gas and carbon source gas to obtain pretreated porous carbon B. The thickness of the outer carbon film of the pretreated porous carbon B is 1.3nm.
[0038] S3. The pretreated porous carbon B is heat-treated under an inert gas and a carbon source gas to obtain modified porous carbon containing metal (metal oxide) and CNTs formed in situ with metal as active sites. The BET ratio of the modified porous carbon to the pretreated porous carbon B is 1:1.16. The heat treatment temperature is 600℃.
[0039] S4. The modified porous carbon is heat-treated under inert gas and silicon / carbon source gas to obtain pre-modified silicon-carbon anode material. The BET ratio of the modified porous carbon to the pretreated porous carbon B is 0.65:1. The heat treatment temperature is 600℃.
[0040] S5. The obtained silicon-carbon anode material is mixed with an inert gas, a binder, and a conductive agent. During the mixing process, the magnetic field strength is controlled by an external magnetic field device to obtain a gradient-distributed silicon-carbon anode sheet. The concentration of metal oxide in the electrode sheet decreases by 0.035 mol / μm from the outside to the current collector direction. The strength of the magnetic field is 0.26T.
[0041] Example 6: A flexible, highly conductive negative electrode sheet and its preparation method, comprising the following steps: S1. Place porous carbon materials and metals (metal oxides) / salts inside a plasma ball milling device, and place the material-carrying area of the ball milling device in an external magnetic field device; S2. The porous carbon is ball-milled in the device for 4.5 hours. During the ball milling process, the magnetic field strength is controlled by an external magnetic field device to obtain pretreated porous carbon A. The mass ratio of the pretreated porous carbon A to the porous carbon material is 1:1.22g. The pretreated porous carbon A is subjected to low-temperature plasma growth of an ultrathin carbon film under inert gas and carbon source gas to obtain pretreated porous carbon B. The thickness of the outer carbon film of the pretreated porous carbon B is 1.3nm.
[0042] S3. The pretreated porous carbon B is heat-treated under an inert gas and a carbon source gas to obtain modified porous carbon containing metal (metal oxide) and CNTs formed in situ with metal as active sites. The BET ratio of the modified porous carbon to the pretreated porous carbon B is 1:1.16. The heat treatment temperature is 600℃.
[0043] S4. The modified porous carbon is heat-treated under inert gas and silicon / carbon source gas to obtain pre-modified silicon-carbon anode material. The BET ratio of the modified porous carbon to the pretreated porous carbon B is 0.65:1. The heat treatment temperature is 600℃.
[0044] S5. The obtained silicon-carbon anode material is mixed with an inert gas, a binder, and a conductive agent. During the mixing process, the magnetic field strength is controlled by an external magnetic field device to obtain a gradient-distributed silicon-carbon anode sheet. The concentration of metal oxide in the electrode sheet decreases by 0.035 mol / μm from the outside to the current collector direction. The strength of the magnetic field is 0.13T.
[0045] Example 7: A flexible, highly conductive negative electrode sheet and its preparation method, comprising the following steps: S1. Place porous carbon materials and metals (metal oxides) / salts inside a plasma ball milling device, and place the material-carrying area of the ball milling device in an external magnetic field device; S2. The porous carbon is ball-milled in the device for 4.5 hours. During the ball milling process, the magnetic field strength is controlled by an external magnetic field device to obtain pretreated porous carbon A. The mass ratio of the pretreated porous carbon A to the porous carbon material is 1:1.22g. The pretreated porous carbon A is subjected to low-temperature plasma growth of an ultrathin carbon film under inert gas and carbon source gas to obtain pretreated porous carbon B. The thickness of the outer carbon film of the pretreated porous carbon B is 1.3nm.
[0046] S3. The pretreated porous carbon B is heat-treated under an inert gas and a carbon source gas to obtain modified porous carbon containing metal (metal oxide) and CNTs formed in situ with metal as active sites. The BET ratio of the modified porous carbon to the pretreated porous carbon B is 1:1.16. The heat treatment temperature is 600℃.
[0047] S4. The modified porous carbon is heat-treated under inert gas and silicon / carbon source gas to obtain pre-modified silicon-carbon anode material. The BET ratio of the modified porous carbon to the pretreated porous carbon B is 0.65:1. The heat treatment temperature is 600℃.
[0048] S5. The obtained silicon-carbon anode material is mixed with an inert gas, a binder, and a conductive agent. During the mixing process, the magnetic field strength is controlled by an external magnetic field device to obtain a gradient-distributed silicon-carbon anode sheet. The concentration of metal oxide in the electrode sheet decreases by 0.028 mol / μm from the outside to the current collector direction. The strength of the magnetic field is 0.28T.
[0049] Example 8: A flexible, highly conductive negative electrode sheet and its preparation method, comprising the following steps: S1. Place porous carbon materials and metals (metal oxides) / salts inside a plasma ball milling device, and place the material-carrying area of the ball milling device in an external magnetic field device; S2. The porous carbon is ball-milled in the device for 4.5 hours. During the ball milling process, the magnetic field strength is controlled by an external magnetic field device to obtain pretreated porous carbon A. The mass ratio of the pretreated porous carbon A to the porous carbon material is 1:1.22g. The pretreated porous carbon A is subjected to low-temperature plasma growth of an ultrathin carbon film under inert gas and carbon source gas to obtain pretreated porous carbon B. The thickness of the outer carbon film of the pretreated porous carbon B is 0.2nm~2nm.
[0050] S3. The pretreated porous carbon B is heat-treated under an inert gas and a carbon source gas to obtain modified porous carbon containing metal (metal oxide) and CNTs formed in situ with metal as active sites. The BET ratio of the modified porous carbon to the pretreated porous carbon B is 1:1.16. The heat treatment temperature is 600℃.
[0051] S4. The modified porous carbon is heat-treated under inert gas and silicon / carbon source gas to obtain pre-modified silicon-carbon anode material. The BET ratio of the modified porous carbon to the pretreated porous carbon B is 0.65:1. The heat treatment temperature is 600℃.
[0052] S5. The obtained silicon-carbon anode material is mixed with an inert gas, a binder, and a conductive agent. During the mixing process, the magnetic field strength is controlled by an external magnetic field device to obtain a gradient-distributed silicon-carbon anode sheet. The concentration of metal oxide in the electrode sheet decreases by 0.036 mol / μm from the outside to the current collector direction. The strength of the magnetic field is 0.31T.
[0053] Example 9: A flexible, highly conductive negative electrode sheet and its preparation method, comprising the following steps: S1. Place porous carbon materials and metals (metal oxides) / salts inside a plasma ball milling device, and place the material-carrying area of the ball milling device in an external magnetic field device; S2. The porous carbon is ball-milled in the device for 4.5 hours. During the ball milling process, the magnetic field strength is controlled by an external magnetic field device to obtain pretreated porous carbon A. The mass ratio of the pretreated porous carbon A to the porous carbon material is 1:1.22g. The pretreated porous carbon A is subjected to low-temperature plasma growth of an ultrathin carbon film under inert gas and carbon source gas to obtain pretreated porous carbon B. The thickness of the outer carbon film of the pretreated porous carbon B is 1.6nm.
[0054] S3. The pretreated porous carbon B is heat-treated under an inert gas and a carbon source gas to obtain modified porous carbon containing metal (metal oxide) and CNTs formed in situ with the metal as active sites. The BET ratio of the modified porous carbon to the pretreated porous carbon B is 1:1.25. The heat treatment temperature is 600℃.
[0055] S4. The modified porous carbon is heat-treated under inert gas and silicon / carbon source gas to obtain pre-modified silicon-carbon anode material. The BET ratio of the modified porous carbon to the pretreated porous carbon B is 0.58:1. The heat treatment temperature is 600℃.
[0056] S5. The obtained silicon-carbon anode material is mixed with an inert gas, a binder, and a conductive agent. During the mixing process, the magnetic field strength is controlled by an external magnetic field device to obtain a gradient-distributed silicon-carbon anode sheet. The concentration of metal oxide in the electrode sheet decreases by 0.063 mol / μm from the outside to the current collector direction. The strength of the magnetic field is 0.12T.
[0057] Comparative Example 1: The negative electrode sheet is prepared according to the method of Example 1, except that the intensity of the electromagnetic field in operation S5 of this example is 3T.
[0058] The BET ratio of the modified porous carbon to the pretreated porous carbon described in this comparative example is 0.25.
[0059] Comparative Example 2: The negative electrode sheet is prepared according to the method of Example 1, except that the intensity of the electromagnetic field in operation S5 of this example is 0.51T.
[0060] The BET ratio of the modified porous carbon to the pretreated porous carbon described in this comparative example is 0.35.
[0061] Comparative Example 3: The negative electrode sheet is prepared according to the method of Example 1, except that the intensity of the electromagnetic field in operation S5 of this example is 0.48T.
[0062] The BET ratio of the modified porous carbon to the pretreated porous carbon described in this comparative example is 0.81.
[0063] Comparative Example 4: The negative electrode sheet is prepared according to the method of Example 1, except that the intensity of the electromagnetic field in operation S5 of this example is 0.68T.
[0064] The BET ratio of the modified porous carbon to the pretreated porous carbon described in this comparative example is 0.75.
[0065] Comparative Example 5: The negative electrode sheet was prepared according to the method of Example 1, except that the corresponding low-temperature plasma growth of ultrathin carbon film experiment was not performed in operation S2 of this example.
[0066] The BET ratio of the modified porous carbon to the pretreated porous carbon described in this comparative example is 0.53.
[0067] Experimental Example Coin cells and CR2032 and 3Ah pouch cells were prepared using the negative electrode materials of Examples 1 to 9 and Comparative Examples 1 to 5, respectively, and the electrical performance of each cell was tested.
[0068] The coin cell battery consists of the following components: Negative electrode: The obtained silicon-carbon negative electrode material containing carbon nanotubes is directly used as the negative electrode material.
[0069] Positive electrode: Lithium metal.
[0070] Electrolyte: 1.2 mol / L LiPF6, solvent is EC / DMC with a molar ratio of 1:1 plus 10 wt% FEC (EC: ethylene carbonate, DMC: dimethyl carbonate, FEC: fluoroethylene carbonate).
[0071] Diaphragm: Celgard 2500.
[0072] The components of a pouch battery are as follows: Negative electrode: The obtained silicon-carbon negative electrode material containing carbon nanotubes is directly used as the negative electrode material.
[0073] Positive electrode: High nickel cobalt manganese oxide lithium NCM811 is used as the positive electrode material. A slurry is prepared according to the weight ratio of positive electrode material, conductive agent SP and PVDF (binder) of 97:2:1, and coated on carbon-coated aluminum foil current collector to prepare the positive electrode.
[0074] Electrolyte: 1.2 mol / L LiPF6, solvent is EC / DMC with a molar ratio of 1:1 plus 10 wt% FEC (EC: ethylene carbonate, DMC: dimethyl carbonate, FEC: fluoroethylene carbonate).
[0075] Diaphragm: Celgard 2500.
[0076] The electrical performance testing methods are as follows: (1) First-cycle negative electrode specific capacity performance test: first-cycle discharge capacity mAh / negative electrode active material mass g; (2) First-cycle coulombic efficiency: First charge capacity / First discharge capacity * 100%; (3) First charge specific capacity: First charge capacity / active material mass (mAh / g); (4) 4C rate discharge capacity retention test: 4C discharge capacity and 1C discharge capacity; (5) DC internal resistance DCR test: Divide the battery capacity and adjust it to 50% SOC. Discharge at 5C for 10s and test the discharge resistance. The resistance DCR = (V0-V10) / I, where V0 is the potential before discharge, V10 is the potential at the 10th second of discharge, and I is the discharge current 5C. (6) Capacity retention test: ① Charging: Charge at a constant current density of 1C to 4.2V and then let stand for 10min; ② Discharging: Discharge at a constant current density of 1C to 2.5V and let stand for 0min. The discharge capacity is recorded as Qn (n=1,2,3......400); ③ Repeat "①, ②" for 400 cycles; The capacity retention rate of the soft pack battery after 400 cycles is: Q400 / Q1; (7) Volume expansion rate test: 400 cycles, fully charged disassembly, micrometer caliper thickness is d2, fresh electrode roll forming thickness is d1, soft pack battery full charge expansion rate calculation after 400 cycles: (d2-d1) / (d1-8), copper foil thickness is 8μm; (8) Lithium plating test: ① Charging: Charge at a constant current density of 2.4C to 4.2V and let stand for 10 minutes; ② Discharging: Discharge at a constant current density of 1C to 2.5V and let stand for 10 minutes; After 10 cycles, charge at a constant current density of 1.6C to 4.2V and disassemble to observe the negative electrode interface.
[0077] (9) Electrochemical impedance spectroscopy (EIS) test: EIS measurements are performed before charge-discharge cycles, with a frequency range of 1 MHz to 0.01 Hz.
[0078] Powder resistivity testing method (four-probe method): Four probes are placed vertically on the surface of the powder sample (or the surface of the tablet). A constant current is passed through the two outer probes, and the voltage drop is measured on the two inner probes. The resistivity is calculated using Ohm's law and the geometric coefficients of the probes.
[0079] The test results are shown in Tables 1 and 2.
[0080] Table 1. Test results of electrical performance of each button cell
[0081] As can be seen from Table 1, considering the effects of Example 9 and Comparative Example 5, and other comparative examples, porous carbon without plasma thin film pre-coating or with a thicker plasma carbon thin film coating exhibits poorer final electrochemical and intrinsic powder conductivity performance. Similarly, considering both experimental examples and comparative examples, the powder resistivity of the examples (0.194~0.326 Ω / cm) is significantly lower than that of the comparative examples (0.376~0.781 Ω / cm). The attenuation mode and intensity of the electromagnetic field can directly affect the redistribution of the conductive network, thereby affecting the intrinsic conductivity and electrochemical performance of the material.
[0082] Table 2. Electrical performance test results of each soft-pack battery
[0083] As shown in Table 2, excessively high magnetic field treatment intensity (Comparative Example 1) affects the aspect ratio of CNTs after growth, causing drastic changes in BET (Bipolar Equivalent Tolerance), thus impacting the overall conductive network performance. The overall conductivity and lithium-ion transport capacity of the material decrease, and electrode volume expansion increases, resulting in reduced capacity retention during long-cycle operation. Furthermore, changes in the decay mode of the magnetic field treatment reshape the CNT growth effect, leading to significant alterations in the overall conductive network distribution and final electrochemical performance. In summary, Tables 1 and 2 indicate that synergistic optimization of the magnetic field treatment and plasma pre-coating carbon film process can effectively improve the intrinsic conductivity and electrochemical performance of the final material.
Claims
1. A method for preparing a flexible, highly conductive negative electrode sheet, characterized in that, Includes the following steps: S1. Place porous carbon materials and metals (metal oxides) / salts inside a plasma ball milling device, and place the material-carrying area of the ball milling device in an external magnetic field device; S2. The porous carbon is ball-milled in the equipment for a certain time. During the ball milling process, the magnetic field strength is adjusted by an external magnetic field device to obtain pretreated porous carbon A. The mass ratio of the pretreated porous carbon A to the porous carbon material is 1:(1.005-1.35). The pretreated porous carbon A is subjected to low-temperature plasma growth of an ultrathin carbon film under inert gas and carbon source gas to obtain pretreated porous carbon B. The thickness of the outer carbon film of the pretreated porous carbon B is 0.2nm~2nm. S3. The pretreated porous carbon B is heat-treated under an inert gas and a carbon source gas to obtain modified porous carbon containing metal (metal oxide) and CNTs formed in situ with metal as active sites. The BET ratio of the modified porous carbon to the pretreated porous carbon B is 1:(1.05~1.35). The heat treatment temperature is 300℃~900℃. S4. The modified porous carbon is heat-treated under inert gas and silicon / carbon source gas respectively to obtain pre-modified silicon-carbon anode material. The BET ratio of the modified porous carbon to the pretreated porous carbon B is (0.35~0.65):
1. The heat treatment temperature is 300℃~900℃. S5. The obtained silicon-carbon anode material is mixed with binder and conductive agent. During the coating process, the magnetic field strength is controlled by an external magnetic field device to obtain a gradient-distributed silicon-carbon anode sheet. The concentration of metal oxide in the electrode sheet decreases from the outside to the current collector direction by 0.001~0.8 mol / μm. The strength of the magnetic field is 0.002~1.5T.
2. The method for preparing a flexible, highly conductive negative electrode sheet according to claim 1, characterized in that, In step S4, the ID / IG ratio of the Raman spectrum of the silicon-carbon anode material is 0.85~1.52, the area of the silicon peak / D peak is 0.013~0.027, and the ratio of the area of the silicon peak / G peak in the Raman spectrum is 0.015~0.
036.
3. The method for preparing a flexible, highly conductive negative electrode sheet according to claim 1, characterized in that, In step S5, the Rct ratio of the electrode after the external magnetic field is applied to the electrode relative to the value when no magnetic field is applied is 1:1.5~4.
5.
4. The method for preparing a flexible, highly conductive negative electrode sheet according to claim 1, characterized in that, In step S1, the porous carbon material has a BET value of 1000~3300m. 2 / g, pore volume 0.6~2.5cm 3 / g, with an average pore size of 1.5~2.1nm.
5. The method for preparing a flexible, highly conductive negative electrode sheet according to claim 1, characterized in that, In step S1, the mass ratio of the porous carbon material to the metal or salt is (80-98.9):(1~10):(1~10), and the molar ratio of the porous carbon material to the metal or salt is (99~99.8):(0.05~0.1):(0.05~0.1).
6. The method for preparing a flexible, highly conductive negative electrode sheet according to claim 1, characterized in that, The ball milling time in step S2 is 0.5~5h, the protective gas is N2 or Ar, and the power output of the equipment is 200~600W; the magnetic field strength in the loading area is 0.03~2T, and the magnetic field attenuation mode is not limited.
7. The method for preparing a flexible, highly conductive negative electrode sheet according to claim 1, characterized in that, In step S2, the BET of the obtained pretreated porous carbon is 0.1~25m. 2 / g, pore volume 0.7~2.3cm 3 / g.
8. The method for preparing a flexible, highly conductive negative electrode sheet according to claim 1, characterized in that, In step S3, the aspect ratio of the CNTs grown in situ on the metal site is 0.03~240.
9. A flexible, highly conductive negative electrode sheet, characterized in that, The flexible, highly conductive negative electrode sheet and its preparation method as described in any one of claims 1-8 are used to prepare the electrode.
10. The application of a flexible, highly conductive negative electrode sheet as described in claim 9 in a lithium-ion battery or a sodium battery.